Statistical Analysis of Effects of Fabric Thickness, Loop Shape Factor, Fabric Tightness Factor and Aerial Weight on Water Vapor Permeability of Single Jersey Polyester Knitted Fabric - Debele, Neway Seboka (International Journal of Scientific Research in Computer Science and Engineering, 2021)
on a daily basis, human being is subjected to different activities. Thus, generation of sweat will occur as the activities are carried out. This will make us uncomfortable. So as to minimize this problem the current research tries to analyze and correlate the effects of fabric thickness, loop shape factor, tightness factor, and fabric aerial weight on water vapor permeability of single jersey polyester knitted fabrics. For conducting the study, sample polyester knitted fabrics have been purchased from local market based on the differences of the stated factors. For statistical analysis, Design expert software version 11 is used. Following Box Behnken design (BBD), 30 experimental runs with 6 center points have been conducted. Accordingly, the experimental analysis shows fabric aerial weight, thickness, tightness factor and loop shape factor significantly affects water vapor permeability of the single jersey polyester knitted fabrics. In addition, the combined effect of fabric aerial weight & tightness factor and the interaction of thickness with tightness factor also affect water vapor permeability significantly. The developed 3D surface graph shows all the stated factors are having an inverse relation with the water vapor permeability behavior of polyester single jersey fabric. Using a confidence level of 95%, the actual versus predicted values are plotted showing the model is adequate and fitting. The calculated correlation coefficient between the actual and predicted value of water vapor permeability is 86.23%. For determination of an optimized water vapor permeability value of the fabrics, regression equation is developed on the basis of actual factors.